ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Organ-on-chip (OoC) technologies and long-acting therapeutics (LATs) are two rapidly advancing fields that have not yet been meaningfully integrated. This review argues that their convergence represents a significant and timely opportunity. LAT development is constrained by a preclinical toolbox that fails to capture the coupled, tissue-dependent processes, depot formation, sustained release, interstitial transport, host response, and local clearance that govern long-acting performance in vivo. OoC platforms can reproduce the physiological microenvironments in which these processes unfold, including barrier structure, controlled perfusion, mechanical cues, and multicellular organization, under reproducible in vitro conditions. This review first maps the scientific and translational challenges of LAT development and the mechanistic requirements any preclinical platform must address. It then shows how the core design principles of OoC technology enable tissue-mimicking platforms that reproduce the microenvironments of the main LAT administration routes. Finally, it brings the two fields together, mapping each LAT requirement directly onto a specific OoC capability, showing that the challenges of scale and long-term culture stability are tractable through defined mitigation strategies, and setting out how the standardization and regulatory alignment now underway can position OoC platforms as credible decision-support tools that complement, rather than replace, existing in vitro release models.